Key role for clumping factor B in Staphylococcus aureus nasal colonization of humans. - Wertheim, H; Walsh, E; Choudhurry, R; Melles, D; Boelens, H; Miajlovic, H; Verbrugh, H; Foster, T; van Belkum, A (Public Library of Science, 2008)
BACKGROUND: Staphylococcus aureus permanently colonizes the vestibulum nasi of one-fifth of the human population, which is a risk factor for autoinfection. The precise mechanisms whereby S. aureus colonizes the nose are still unknown. The staphylococcal cell-wall protein clumping factor B (ClfB) promotes adhesion to squamous epithelial cells in vitro and might be a physiologically relevant colonization factor. METHODS AND FINDINGS: We define the role of the staphylococcal cytokeratin-binding protein ClfB in the colonization process by artificial inoculation of human volunteers with a wild-type strain and its single locus ClfB knock-out mutant. The wild-type strain adhered to immobilized recombinant human cytokeratin 10 (CK10) in a dose-dependent manner, whereas the ClfB(-) mutant did not. The wild-type strain, when grown to the stationary phase in a poor growth medium, adhered better to CK10, than when the same strain was grown in a nutrient-rich environment. Nasal cultures show that the mutant strain is eliminated from the nares significantly faster than the wild-type strain, with a median of 3 +/- 1 d versus 7 +/- 4 d (p = 0.006). Furthermore, the wild-type strain was still present in the nares of 3/16 volunteers at the end of follow-up, and the mutant strain was not. CONCLUSIONS: The human colonization model, in combination with in vitro data, shows that the ClfB protein is a major determinant of nasal-persistent S. aureus carriage and is a candidate target molecule for decolonization strategies.